Idiosyncratic risk and anomaly persistence on the Johannesburg Stock Exchange (JSE). Issue 1 (2nd January 2016) - Page, Daniel; Britten, James; Auret, Christo
ABSTRACT: This study examines arbitrage costs and the persistence of the size, value and momentum premiums on the Johannesburg Stock Exchange (JSE). Two arbitrage costs are considered: transaction and holding costs. Transaction costs refer to indirect and direct costs of engaging in arbitrage. Holding costs relate to the level of idiosyncratic risk that arbitrageurs expose themselves to in pursuit of an individual strategy. We examine monthly price and accounting data of all JSE listed shares over the period 1 January 1992 to 30 November 2014. The effects of idiosyncratic risk are evaluated with asymmetric and GARCH-in-mean models using zero-cost portfolio return series. The results reveal significant and persistent value and momentum effects. The value premium is highly sensitive and negatively related to direct transaction costs. Conversely, momentum has greater sensitivity to indirect transaction costs and displays a negative relationship. An increase in idiosyncratic risk results in an increase in the value premium. However, the momentum premium does not react positively to an increase in idiosyncratic risk. The findings imply that the costs of arbitrage play a large role in the persistence and existence of the value premium, yet the same cannot be said for medium-term momentum in share prices.